“Hot” and “Cold” Cognition in Users of Club Drugs/Novel Psychoactive Substances - Savulich, George; Bowden-Jones, Owen; Stephenson, Robert; Brühl, Annette B.; Ersche, Karen D.; Robbins, Trevor W.; Sahakian, Barbara J. (Frontiers in Psychiatry, 2021)
Novel psychoactive substances (NPS) are popular "club/party" drugs that first attracted attention in the UK in 2009 and remained legal until the 2016 Psychoactive Substances Act criminalized their distribution. Unlike “traditional” illicit drugs, very little is known about the influence of their analogues on neuropsychological functioning. We characterized the cognitive and emotional profile of NPS/polydrug users using the Cambridge Neuropsychological Test Automated Battery (CANTAB) and EMOTICOM test battery in adult male (aged 20-49 years) recreational users without psychiatric comorbidities (n=27; "psychonauts"), service users attending a UK specialist "Club Drug" Clinic for problematic use (n=20) and healthy control volunteers without significant drug-taking histories (n=35). Tasks were selected to distinguish “hot” cognitive processes that are highly influenced by emotion from “cold” cognitive processes that are largely independent of emotional influence. Both user groups reported significantly higher sensation-seeking traits compared with non-users. Recreational NPS users demonstrated more risk-taking behaviour compared with controls and treatment-seeking NPS users showed poorer learning, episodic memory and response inhibition compared with the other two groups. These effects persisted, when controlling for age, intelligence, alcohol and cannabis use severity, nicotine dependence, trait anxiety, depression, childhood adversity, impulsivity and sensation seeking. Overall, recreational NPS users showed elevated "hot" (emotion-laden) cognition in the absence of "cold" (non-emotional) cognitive deficits, whereas "cold" cognitive dysfunction was pronounced in individuals seeking treatment for problematic NPS use. High trait impulsivity and poor self-control may confer additional risk to NPS/polydrug use severity and separate those seeking treatment from those using NPS recreationally.